Constitutional Responsibility for Regulating Food Sovereignty - Rozi, Fahrur; Safa’at, Muchamad Ali; Istislam, Istislam (International Journal of Business, Law, and Education, 2024)
This study aims to analyze the constitutional responsibility for food sovereignty and self-reliance as regulated in Law Number 6 of 2023 concerning Job Creation. The type of research used is normative research with a statute approach and conceptual approach. Based on the results of the research, it shows that the enactment of Law No. 6 of 2023 concerning Job Creation, especially in terms of food, has implications for the goals of food sovereignty and self-reliance in Indonesia, which were previously stipulated in Law No. 18 of 2012 concerning Food. It is feared that this will affect the decline in farmers' welfare levels due to the absence of restrictions on food imports. The position of food imports parallel to domestic production and national food reserves no longer reflects the essence of food sovereignty. In this problem, the constitutional responsibility related to food sovereignty is to review Law No. 6 of 2023 on Job Creation to ensure the achievement of public welfare.